Public-Private Partnerships: Success and Failure Factors for In-Transition Countries - Urio, Paolo (Hamilton Books, 2010)
Public-Private Partnerships aims to discover the conditions under which public private partnerships may provide a viable alternative to the provision of public services and infrastructures by the state, while achieving efficient, sustainable, peaceful, and equitable development in four transition countries: China, Poland, Russia, and Ukraine. These countries have experienced command economy under communist rule for at least thirty years. They have only recently introduced market mechanisms. In spite of a huge literature in favor of public private partnerships in the west, scientific empirical evidence is generally mixed and balanced. Success or failure depends upon many factors that need to be identified and analyzed. Moreover, economic performance may be achieved at the expense of other criteria such as equity, public scrutiny, and accountability. This research (a cooperation between the University of Geneva and the United Nations) is the first attempt to evaluate public private partnerships based upon a review of the literature in Europe, documentary analysis, and in-depth interviews in the four countries with representatives of the public and private sectors, as well civil society organizations.